Reproductive Health Problems in Women (Texas Journal of Medical Science, 2026)
This article provides a scientific analysis of reproductive health problems in women, their causes, risk factors, and impact on overall health. Reproductive health is closely related to a woman’s general wellbeing, and its disorders are manifested through various gynecological conditions, including menstrual cycle disorders, infertility, inflammatory diseases, and hormonal imbalance. The article also highlights the role of social, environmental, and occupational factors in the development of these issues. The study examines preventive measures, modern diagnostic methods, and the importance of a healthy lifestyle in maintaining women’s reproductive health. Based on the findings, practical recommendations have been developed